A escuta de sujeitos adolescentes que vivenciaram o abrigamento: contribuições psicanalíticas - Santos, Carla Pinhassi (2007)
This essay object is to ponder over the sheltered housing for adolescents in São Paulo city based on psychoanalytic theory references. To institutionalize adolescents has been a common and repeated practice since Brazil was a colony. During our history that kind of attendance was changed many times because of new laws and public policies. The teenagers that live in that kind of housing come from the poorest part of population in our society. Nowadays, there is a significant number of shelters which aim to attend this part of the population, and a great number of sheltered children as well. This essay aim to listen to individuals who live or have lived under those conditions during their adolescences. What they say, based on psychoanalytic theory, will enable us to understand how they felt the experience, which links they built up, whit consequences were brought to their subjective perception and how their personal growth was affected. Having analyzed that material we could reflect on the way sheltered-housing works and its importance in our society